ANALISIS PENGARUH VARIABEL SPESIFIK BANK TERHADAP PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA (Studi pada Bank Umum Syariah dan Unit Usaha Syariah di Indonesia Periode 2010-2013) - Lindasari, Melati; Demi Pangestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2016)
Competition among Islamic banks increasingly stringent directly or indirectly affect the achievement of the profitability of Islamic banks. In addition, the ability to generate profits become an important indicator to measure the ability of Islamic banks to compete in the long term. This study aims to obtain empirical evidence about the effect of the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Operational Efficiency Ratio (OER), Financing to Deposits Ratio (FDR), Net Operating Margin (NOM) and Size to the Return On Assets (ROA) and to determine the variable that give the dominant influence on the profitability of Islamic banks. The populations used in this study were all Islamic Banks operating in Indonesia. The sample used in this study consists of 8 islamic commercial banks and 3 sharia business units in the Indonesian period 2010-2013. The data analyses employed the use of multiple linear regression which is previously performed classical assumption, such as normality test, multicollinearity test, autocorrelation test, and heteroskedastisitas test. Hypothesis testing by using the F test and T test.The results from this study indicates that CAR, REO and FDR has significant negative influences on ROA. NOM significant positive effect on ROA and NPF did not significant positive effect on ROA. Meanwhile, Size did not significant negative effect on ROA and the use of a dummy variable type did not significant negative effect on ROA. The amount of determination degree test (Adjusted R Square ) is equal to 0,714. This means the independent variables such as CAR, NPF, REO, FDR, NOM and Size have the impact on ROA ofÂ 71.4% . Meanwhile , the remaining 28.6% is explained by other variables outside the model of this study .